Search of the promising species of subfamily Amygdaloideae and Pyroideae using the chemotaxonomy - Sydora, Natalia; Kovaleva, Alla; Goncharov, Alexandr (ScienceRise: Pharmaceutical Science, 2018)
World flora has more than 1000 species of the genus Сrataegus L., more than 30 species belong to the subgenus Prunus L., genus Malus Mill. has 100 species, subgenus Cerasus Juss. includes more than 150 species. Despite the diversity of species and a sufficient resource base, only a few representatives of the genus sufficiently researched and found their use as sources of biologically active substances (BAS). Aim of research. To conduct a chemotaxonomic study of representatives of the genus Сrataegus L., Prunus L., Malus Mill., Cerasus Juss.; to establish a promising sources of biologically active substances for the drugs production. Materials and methods. Chemotaxonomic study was carried out using the method of the graph analysis. The chemomarkers were phenolic compounds and terpenoids, identified in the generative and vegetative organs of the representatives of the genus Сrataegus L., Prunus L., Malus Mill., Cerasus Juss. The terpenoids and organic acids were identified by a chromatography-mass-spectrometric method on an Agilent Technology 6890N chromatograph with a 5973N mass-spectrometric detector. Flavonoids and hydroxycinnamic acids were detected by chromatography. Results. The chemical profiles of vegetative and generative organs of 34 species of the genus Сrataegus L. are established, 5 species of the genus Prunus L., 7 species of the genus Malus Mill., 4 species of the genus Cerasus Juss. The promising species of hawthorn, wich accumulated a general group BAS of genus was detected. Conclusion. According to the results of a chemotaxonomic study of representatives of subgenus Amygdaloideae and Pyroideae was detected a promising sources of biologically active substances (BAS) among species of the genus Crataegus L., Prunus L., Malus Mill. and Cerasus Juss. The chemical profiles are forming flavonoids, terpenoids and aromatic acids. The promising species of hawthorn was added to the complex «Kratophyt»